Short Stature in Children Visiting Endocrine Out Patient Department of Kanti Children’s Hospital, Nepal: A retrospective review - Yadav, Anupama Kumari; Karki, Subhana Thapa (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: The causes of Short Stature in children are different in different countries. It can vary from endocrine to non-endocrine. This study was conducted to identify the causes of short stature in children who are brought in Endocrine Out Patient Department of Kanti Children’s Hospital. Methods: This is a retrospective study done at Endocrine Out Patient Department of Kanti Children’s Hospital for ten year duration. One Hundred and Twenty five Children who were brought with chief complain of not gaining height were included. Children’s were evaluated for causes of short stature. Results: Male and Female ratio was 1.2:1. The commonest cause seen was Familial Short Stature 41(32.8%), Constitutional 22(17.6%), Hypothyroidism 20 (16%), Syndromic 13 (10.4%), Skeletal Dysplasia 10 (8%), Malnutrition 10 (8%), Chronic Diseases 7 (5.6%) and Growth Hormone Deficiency 2 (1.6%). Conclusions: This study showed Familial and Constitutional short stature as leading cause of short stature. Hypothyroidism and Malnutrition account for significant percentage which are treatable cause. Down’s syndrome(40%) and Turner Syndrome(7.6%) are the main genetic causes of short stature.